Richness and community structure of sand dunes (restinga) in Santa Catarina: subsidies for ecological restoration - Pedro Yuri Ribeiro; João Carlos Ferreira de Melo Júnior (Acta Biológica Catarinense, 2021)
The coast of Balneario Piçarras city (Santa Catarina) is being constantly degraded by human action. This study aimed to characterize the richness and vegetation structure of two areas of herbaceous restinga (preserved and degraded) of the coastal plain of this city. The flora was mapped by using the patrolling method. Identification was done by comparative morphology and specialized bibliography. The phytosociology was based on the plot method with allocation oriented parallel to the coast line. There were 48 species, 44 genera and 22 families identified. Fabaceae, Asteraceae and Poaceae are the richest families. The H’ index was 3.9 in the preserved area and 2.1 in the degraded area. The community structure was represented by eight and 16 species in the degraded and preserved areas, respectively. In degraded areas, species as Spartina ciliata, Ipomoea pes-caprae, Sphagneticola trilobata and Paspalum vaginatum have the greater importance of coverage, structuring the community. In the preserved area, the organization structure of the community is given by Canavalia rosea, Remirea maritima, Stenotaphrum secundatum, Spartina ciliata and Acicarpha spathulata species. These species are considered pioneers and with a great potential of fixing dunes, which reflects their importance to the achievement of a future restoration work of the damaged area of the restinga in question.